2022
DOI: 10.1002/adhm.202200251
|View full text |Cite
|
Sign up to set email alerts
|

Chondro‐Inductive b‐TPUe‐Based Functionalized Scaffolds for Application in Cartilage Tissue Engineering

Abstract: Osteoarthritis is a disease with a great socioeconomic impact and mainly affects articular cartilage, a tissue with reduced self-healing capacity. In this work, 3D printed 1,4 butanediol thermoplastic polyurethane (b-TPUe) scaffolds are functionalized and infrapatellar mesenchymal stem cells are used as the cellular source. Since b-TPUe is a biomaterial with mechanical properties similar to cartilage, but it does not provide the desired environment for cell adhesion, scaffolds are functionalized with two metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 65 publications
0
9
0
Order By: Relevance
“…The synthetic material b‐TPUe shows promise for cartilage engineering, but it does not typically have sufficient bioactivity to allow for clinical use. This study showed that 3D printed b‐TPUe scaffolds decorated with collagen I or PBA had increased cell attachment and proliferation, increased chondrogenic differentiation potential without the use of differentiation medium or growth factors 65 …”
Section: Cartilagementioning
confidence: 82%
“…The synthetic material b‐TPUe shows promise for cartilage engineering, but it does not typically have sufficient bioactivity to allow for clinical use. This study showed that 3D printed b‐TPUe scaffolds decorated with collagen I or PBA had increased cell attachment and proliferation, increased chondrogenic differentiation potential without the use of differentiation medium or growth factors 65 …”
Section: Cartilagementioning
confidence: 82%
“…Regenerative engineering approaches to treat full thickness chondral defects or OCDs (extending from articular cartilage surface into the underlying subchondral bone) has garnered ample attention in recent literature (Table 2). [58][59][60][61][62][63][64][65][66][67][68][69][70][71] For example, Song et el. fabricated a templated hydrogel scaffold based on human-like collagen that exhibited an interconnected porous structure through the use of a bovine serum albumin (BSA) porogen.…”
Section: Articular Cartilagementioning
confidence: 99%
“…3D printing may be used to obtain scaffolds with controlled architecture and arrangement of biochemical cues. [63][64][65][66][67][68][69][70][71] Castilho et al created a microfiber (polycaprolactone (PCL))-reinforced gelatin-methacrylate (GelMA) hydrogel wherein the microfibers were oriented in the direction of natural collagen fibers based on depth-wise properties. 66 This promoted cartilage-like stress relaxation, and the application of mechanical forces stimulated the production of collagen II and GAGs in the absence of bioactive factors.…”
Section: Articular Cartilagementioning
confidence: 99%
See 2 more Smart Citations